TECHNIQUES OF RECYCLING AND MARBLING OF PAPER - Thode Filho, Sérgio; Costa, Ana Paula da Silva da; Rodrigues, Israel; Andrade, Azarias Machado de; Sena, Marcelo Monteiro Fonseca de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
A study on the gravimetric composition of municipal solid waste in Brazil, has the role as the third place in the ranking of waste with 13.1% of the total composition. The objective of this paper is to present a technique of marbling paper recycling and using Basic carboxymethylcelulose input. First acquired up to 50 sheets of paper already used and cut into small pieces. Subsequently, they were placed in plastic bucket with about two liters of water. This mixture was allowed to stand for 24 hours. For technical marbling of the recycled paper used is carboxymethylcelulose, water, oil-based ink of various colors. The result of the processing methodology is described in a uniform paper, A4 format with a fine rough texture throughout leaf structure, good mechanical resistance to traction without the aroma a pale white color (depending on the paper to be recycled), suitable writing and other applications. The technique of marbling, adds value to the material and suggests different applicability, including artistic.